Starość – szansa czy zagrożenie dla rozwoju moralnego człowieka w ocenie stoików - Siwicka, Małgorzata (Vox Patrum, 2011)
The old age in the ancient culture of Greece and Rome, in contrast to popular opinion, appears not to be held in high esteem by everyone. This observation can be illustrated by a lot of sources in the Greek and Roman literature. The old age has been considered as difficult and troublesome both for persons, whose were afflicted by this age, and for their family, friends and all attendants. This period of human life has been exposed to illness and the other afflictions – weakness of body and mind, less intense clarity and precision of thought. Consequently, the old people would take active part in the social and political life only in this case, when they were in good health, in good physical and mental condition. Because of this in Greek and Roman literature can be found a lot of lamentations and complaints of the old age. Only Plato and representatives of new stoic school – Seneca, Epictetus and Marcus Aurelius formulated opposite theories about the old age. According to Stoics’ perceiving of the world and the time and cyclical changes of them, the man’s nature and condition from his birth directs inevitably to his death. The whole world is ruled by God and nothing in it happens without his will. So the good and wise man will accept everything, as well the old age, and all its disadvantages. This acceptance off all that happens will bring man peace of mind and protection against whatever he may suffer. The old age – for a lover of wisdom is an occasion to develop and grow up his moral virtues and to improve his character. This intellectual and ethical process issues from human reason, which is a part of divine reason, pervasive all things in the world and all men. The Stoics warn against a danger of a moral decline and in the old age. This corruption would be caused by direction of man’s attention to the shortness of life instead of the improving his character. The number of years of human life appears not to be important for Stoics. They condemn an aim for long life, if it not connected with an aspiration for wisdom.